A Genome-Wide Association Study for Coronary Artery Disease Identifies a Novel Susceptibility Locus in the Major Histocompatibility Complex - Davies, Robert W.; Wells, George A.; Stewart, Alexandre F.R.; Erdmann, Jeanette; Shah, Svati H.; Ferguson, Jane F.; Hall, Alistair S.; Anand, Sonia S.; Burnett, Mary S.; Epstein, Stephen E.; Dandona, Sonny; Chen, Li; et al. (Circulation. Cardiovascular genetics, 2012)
BACKGROUND—Recent genome-wide association studies (GWAS) have identified several novel loci that reproducibly associate with coronary artery disease (CAD) and/or myocardial infarction risk. However, known common CAD risk variants explain only 10% of the predicted genetic heritability of the disease, suggesting that important genetic signals remain to be discovered. METHODS AND RESULTS—We performed a discovery meta-analysis of 5 GWAS involving 13 949 subjects (7123 cases, 6826 control subjects) imputed at approximately 5 million single nucleotide polymorphisms, using pilot 1000 Genomes–based haplotypes. Promising loci were followed up in an additional 5 studies with 11 032 subjects (5211 cases, 5821 control subjects). A novel CAD locus on chromosome 6p21.3 in the major histocompatibility complex (MHC) between HCG27 and HLA-C was identified and achieved genome-wide significance in the combined analysis (rs3869109; pdiscovery=3.3×10, preplication=5.3×10pcombined=1.12×10). A subanalysis combining discovery GWAS showed an attenuation of significance when stringent corrections for European population structure were used (P=4.1×10 versus 3.2×10), suggesting that the observed signal is partly confounded due to population stratification. This gene dense region plays an important role in inflammation, immunity, and self–cell recognition. To determine whether the underlying association was driven by MHC class I alleles, we statistically imputed common HLA alleles into the discovery subjects; however, no single common HLA type contributed significantly or fully explained the observed association. CONCLUSIONS—We have identified a novel locus in the MHC associated with CAD. MHC genes regulate inflammation and T-cell responses that contribute importantly to the initiation and propagation of atherosclerosis. Further laboratory studies will be required to understand the biological basis of this association and identify the causative allele(s).